Comprehension Monitoring, Appraisal Confidence and Self-efficacy in EFL Reading: A Correlational Study from Nepal - Bastola, Madhu Neupane (SCHOLARS: Journal of Arts & Humanities, 2020)
The current study explored the relationships among English as a Foreign Language (EFL) learners’ comprehension monitoring, appraisal confidence, reading self-efficacy and EFL reading comprehension performance. First, 203 students reported their comprehension monitoring and reading self-efficacy. Then they took an EFL reading comprehension test and reported their appraisal confidence immediately after answering each question. Students’ comprehension monitoring, appraisal confidence and reading self-efficacy were found to be far higher than their average reading comprehension performance. Similarly, the students with a high level of reading comprehension tended to be better at monitoring comprehension and were more self-efficacious than those who performed poorly in the test. Finally, significantly positive correlations were found among comprehension monitoring, appraisal confidence, reading self-efficacy and EFL reading comprehension performance.